Systematic Literature Review: Implementation COBIT as a Best Practice of Electronic Based Government System Governance - Puspitaningrum, Ari Cahaya; Fitrani, Laqma Dica; Sintiya, Endah Septa (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Presidential Regulation of the Republic of Indonesia No. 95 of 2018 told that the implementation of SPBE is recommended to create clean, effective, transparent and accountable government governance as well as quality and trustworthy public services. This research use the systematic literature review (SLR) method by reviewed the implementation of COBIT best practices in various government organization in Indonesia in the last 5 years. This was done by analyzed each selected study and it can be concluded that there were 27 scientific journal studies and 3 conference studies. Analysis of 30 studies resulted in several groupings of studies, those are based on study objectives, frequently found focus areas, and frequently used domains. Based on the grouping of selected studies, it can be seen that there are 2 different objectives in using COBIT in government agencies, 1) the objective of measuring the level of maturity and capability of IT governance and 2) the objective of designing an IT governance system. The domains most frequently found in the selected studies are APO and DSS. Apart from that, this research also found a focus area that is often found, namely IT services and there are recommendations for further research based on being able to evaluate and design IT governance in the COBIT domain which is often found based on the focus area.